Relevance of data analytics in sustainable fisheries management: An evidence-based study - Isaac Lukambagire; Baker Matovu; Bhavani Rao R.; Meltem Alkoyak-Yildiz; Remya S.N.; Isaac Sarfo (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The value of fish resources to socioeconomic development is immense. However, there is growing evidence that loss of quality in the marine environments e.g. marine waters at sea and coastal freshwater zones is threatening the availability of livelihood resources e.g. fish resources evidenced by the dwindling fisheries resources that promote sustainable livelihood. Aware of this, several fisheries’ institutions, governments, and local users have come up with several strategies to boost marine water environment management and promote sustainable fishing. Unfortunately, most of the initiatives have not fully managed to eradicate unsustainable practices e.g. marine water pollution, which leads to loss of wild catches and to unsustainable fishing practices.